Practical stability of switched uncertain nonlinear systems using state-dependent switching laws. (November 2015) - Mendoza-Torres, Angelica; Cervantes, Ilse; Cabrera-Ibarra, Hugo
Abstract: In this paper, it is proven that a state dependent switching law designed for integrator switched systems can be used to stabilize complex switched uncertain nonlinear systems as well as a class of impulsive systems, provided that the upper bound of the uncertainty terms satisfy a relationship with the nominal system parameters estimation of the nominal system parameters. In order to establish such a result, firstly, a switching law is proposed to ε -practically stabilize an uncertain integrator switched system; secondly, the proposed switching law is used to prove that the trajectories of a general class of uncertain nonlinear systems are ε -practical stable and connections to switched nonlinear impulsive systems are revealed. Numerical simulations allow us to illustrate the proposed stability results and an example in a power electronics device is used to show the applicability of the proposed state-dependent switching control strategy.